Dielectric Strength of Kenaf/Glass Fiber Reinforced up Hybrid Composites used as Insulator - Bassam A.; Ansari M.N.M.; Nazim A.R.M.; Thilageshwaran S.; Vinoth K.S.; Abdullah F.; Afeefah Nordin N. (Institute of Electrical and Electronics Engineers Inc., 2023)
Aspect ratio; Climate change; Dielectric materials; Fiber reinforced plastics; Glass fibers; Hemp; Hybrid materials; Kenaf fibers; Polymers; Volume fraction; Ceramic insulators; Circular cross-sections; Dielectric strengths; Glass fiber reinforced polymer; High voltage transmission lines; Hybrid composite materials; Polymeric housing; Unsaturated polyester; Dielectric properties of solids